The Influence of Price Perception, Store Atmosphere, and Location on Purchase Decisions at Retjeh Kopi Coffee Shop in Mojokerto - Amma Fizka Zakiyatul Miskiya; Zumrotul Fitriyah (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2025)
This study aims to determine the effect of price perception variables, store atmosphere and location on purchase decisions at Retjeh Kopi Coffee Shop in Mojokerto. The population in the study were consumers of coffee shop Retjeh Kopi Mojokerto. The sample taken was 100 respondents using accidental sampling technique. For data collection is done through observation, interviews, collecting questionnaires and literature studies. The data analysis method uses component based structural equation modeling or SEM with Partial Least Square or PLS analysis tools. The results show that price perception, store atmosphere, and location partially have a positive and significant effect on purchase decisions. The implications of this research are important for business people, especially coffee shop businesses. Understand that price perception, store atmosphere and location have an important influence on making purchasing decisions. Coffee shop businesses must pay attention to the prices set with the products offered in order to foster a good perception in the minds of consumers. In addition, the store atmosphere must be considered starting from the atmosphere, music, lighting, layout and others must be made comfortable so that consumers want to linger in the store for a long time. And the selection of a strategic location is also very important to make it easier for consumers to reach the coffee shop.